“Gente-grande”: denúncia da pequenez dos adultos - Juracy Assmann Saraiva; Ernani Mügge (Estudos de Literatura Brasileira Contemporânea)
Based on the idea that the literary text is the result of an author’s critical reflection on reality as well as a work of l anguage, activities that find their counterpart on the reader, this article analyses the representation process instituted in the short story “Gente - grande”, by Domingos Pellegrini. The communicational structure in “Gente - grande” and its narrative strategi es lead the reader to share the character’s drama, due to the conflictive divorce of their parents. In parallel, the short story mobilizes the reader to identify similar situations in the contemporary context, while it instigates him to focus on the compo sitional elements, which constitute the articulation between fiction and reality. As a result, the image of the astonished child becomes prominent because of the adults’ incoherence and the violation of the family’s harmony, a harmony which childhood deser ves. Thus, the short story written by Domingos Pellegrini executes the forming function of art, since it acts on the reader, drawing his/her attention to human dramas, particularly those of children.